Roa Fish Sambal Innovation For Culinary MSMEs In Sidoarjo - Achmad Inzaghi Montella Putra; Siti Aisyah; Umi Nur Hastuti; Yudi Prasetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the innovation of processing roa fish into chili sauce by MSME actors in Sidoarjo, as well as evaluate the market potential and the economic-social impact it causes. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation of culinary MSME actors in the Candi area, Sidoarjo. The results of the study show that the production process of roa fish sauce is carried out systematically through the stages of selecting raw materials, processing chili sauce, and packaging. This product received a very positive market response, with the majority of consumers expressing high interest in the unique taste of chili sauce. In addition to increasing the income of business actors, this innovation also encourages job creation, women's empowerment, and the involvement of the younger generation in the entrepreneurial ecosystem. Roa fish sauce not only strengthens the competitiveness of local products in the midst of increasingly fierce market competition, but also strengthens the role of MSMEs in the growth of culinary-based creative economy.